Favorable 2 '-substitution in the loop region of a thrombin-binding DNA aptamer - Awachat, Ragini; Wagh, Atish A.; Aher, Manisha; Fernandes, Moneesha; Kumar, Vaijayanti A. (Bioorganic & Medicinal Chemistry Letters, 2018)
Simple 2'-OMe-chemical modification in the loop region of the 15mer G-rich DNA sequence GGTTGGTGTGGTTGG is reported. The G-quadruplex structure of this thrombin-binding aptamer (TBA), is stabilized by single modifications (T -> 2'-OMe-U), depending on the position of the modification. The structural stability also renders significantly increased inhibition of thrombin-induced fibrin polymerization, a process closely associated with blood-clotting. (C) 2018 Elsevier Ltd. All rights reserved.

2 `-5 `-Isomerically linked thrombin-binding aptamer (isoTBA) forms a stable unimolecular parallel G-quadruplex in the presence of Sr2+ Ions - Wagh, Atish A.; Fernandes, Moneesha (ChemistrySelect, 2019)
The ability of the isomeri 2 `-5 `-phosphodiester-linked thrombin-binding DNA aptamer pentadecamer G(2)T(2)G(2)TGTG(2)T(2)G(2) (isoTBA), to fold into G-quadruplex structures in the presence of different mono- and divalent cations is reported. Strikingly, Sr2+ ions cause isoTBA to fold into a stable parallel unimolecular G-quadruplex, in contrast to the antiparallel unimolecular G-quadruplex fold observed in the presence of K+. IsoTBA being advantageously more stable than TBA to nuclease degradation, may thus be useful in the selective detection of Sr2+ ions, which it can sense with a detection limit of similar to 55 mu M.
Keywords: 2 `-5 `-phosphodiester; parallel DNA G-quadruplex; strontium binding; thrombin-binding aptamer; unimolecular G-quadruplex

Replacement of loop residues in TBA by an abasic ethylene glycol spacer: effect on stability, structure and function** - Wagh, Atish A.; Ghalawat, Monika; Fernandes, Moneesha (ChemistrySelect, 2021)
This article describes the synthesis of ethyleneglycol (E) phosphoramidite and its incorporation into the thrombin binding aptamer (TBA) sequence at loop positions. Circular dichroism (CD) study revealed no major disturbances in the secondary structure of TBA by the abasic E unit and the derived oligomers exhibited a typical antiparallel chair-like conformation similar to that of TBA. UV and CD spectroscopy, together with anti-coagulation and HPLC studies revealed that although nuclease stability was enhanced, and anti-coagulation reasonably good, the thermal stability of the quadruplexes was adversely affected.
Keywords: aptamers; clotting time; ethylene glycol spacer; G-quadruplexes; nuclease stability